Batch adsorption study of bentazon herbicide from aqueous solution using coconut activated carbon - J. M. Salman; A. A Muhammed; A. A. Shahad (Journal of Madenat Alelem University College, 2011)
Adsorption study of bentazon from aqueous solution using commercial coconut activated carbon (CCAC) as adsorbent has been carried out in batch process. The experimental data were analyzed by the Langmuir isotherm, the Freundlich isotherm and the Temkin isotherm. Equilibrium data fitted well with the Langmuir model with maximum adsorption capacity of 111.1 mg/g at 30°C when the initial concentration was 25–250 mg/L. Pseudo-first and pseudo-second-order kinetics models were tested with the experimental data, and pseudo-second-order kinetics was the best for the adsorption of bentazon by CCAC with coefficients of correlation R2 ≥0.988 for all initial bentazon concentrations studied.